Contribution of xeroderma pigmentosum complementation group D gene polymorphisms in breast and ovarian cancer susceptibility: A protocol for systematic review and meta analysis. Issue 21 (22nd May 2020) - Tian, Yumei; Lin, Xiaojuan; Yang, Fan; Zhao, Jitong; Yao, Kui; Bian, Ce
Abstract: Background: The role of xeroderma pigmentosum complementation group D (XPD) gene polymorphisms in breast and ovarian cancer development has long been controversial and existing data were inconsistent. Here, we conducted a comprehensive systemic review and meta-analysis to better clarify the association. Methods: Relevant case-control studies published in electronic data base from October 1999 to September 2019 were assessed. The statistical analyses of the pooled odds ratios (ORs) and the corresponding 95% confidence intervals (95%CIs) were calculated by using Revman 5.2 software (Cochrane Collaboration, Copenhagen). Results: 31 articles including 38 case-control studies and 2 XPD polymorphisms (rs1799793 and rs238406) were analyzed. The results showed statistical significance in heterozygous mutants among Asian population for rs1799793 (GA vs GG + AA: OR = 1.38, 95%CI = 1.21–1.56), and Caucasian population for rs238406 (CA vs AA + CC: OR = 0.63, 95%CI = 0.49–0.80), while the rest comparisons including overall groups and subgroups stratified by cancer types and ethnicity failed to indicate any association with breast and ovarian cancer risk. Conclusions: The current meta-analysis suggested no concrete correlation of XPD rs1799793(G/A) and rs238406(C/A) polymorphisms with breast cancer or ovarian cancer susceptibility. However, it indicated that heterozygous genotypes might share different pathophysiologic mechanism from not only homozygous wildtypes but also homozygous mutants. More case–control studies with well-adjusted data and diverse populations are essential for validation of our conclusion.